Use of Cybergogy in Improving Reading Comprehension among High School Students: A Systematic Literature Review - Odvina, Ramilyn A.; Baylon, Lemalyn A.; Ayop, Rachelle Mae M.; Evardo Jr, Orville J. (MO.RI Publishing, 2024)
This systematic literature review investigates the role of cybergogy in enhancing reading comprehension among high school students, driven by the increasing use of digital tools in education. The review analyzed 25 studies, revealing that cybergogy offers significant benefits, such as the practical use of digital tools, flexible learning environments, and improved teaching quality. However, it also identifies several challenges, including digital distractions, insufficient foundational reading skills, logistical and technological constraints, and the dual impact of technology on reading habits. These findings underscore the necessity for a balanced approach to integrating cybergogy, emphasizing the need for targeted interventions to address the identified challenges, enhanced professional development for educators, and improved technological infrastructure. By focusing on these areas, schools can make better use of cybergogy to improve reading skills and help students succeed academically.